How to avoid interfering electrochemical reactions in ESI‐MS analysis. (27th February 2019) - Lübbert, Christian; Peukert, Wolfgang
Abstract: The presence of electrochemical reactions occurring in an electrospray processes at the point where the current enters the liquid is discussed since the early 1990's. This current transfer to the liquid results in oxidation or reduction of either electrolyte species in the liquid sprayed or of the electrode material in contact with the liquid. As a result, new chemical species are generated. These products of the electrochemical reaction might be detected as altered species in mass spectra; they might be volatile and not recognized at all or accumulate on the electrode surface and cause cross contamination later on. In other cases, it might happen that the products of the electrochemical reactions are the only detectable species formed from an otherwise nondetectable analyte. An electrospray setup in which electrochemical reactions do not interfere with the analyte under investigation excludes the electrochemical reaction as source of sample contamination and sample altering and may serve as reference setup for experiments focused on the electrochemical reaction itself. We present a simple and inexpensive current coupling approach and specify operation conditions for which any impact of the electrochemical reaction on the sample under investigation is inherently excluded. On the basis of a practical example, we show the impact of the electrochemical reaction on sample composition and demonstrate the benefit of using the proposed current coupling method. Because of the obvious benefit of this method and its simple realization, it has the potential to be employed as standard feeding approach, especially for electrosprays operated at small flow rates.